The evolution of transnational sustainability governance through a systems theory lens - Karin Buhmann (Oñati Socio-Legal Series)
This article applies Luhmann’s systems theory approach to the argumentative dynamics of the processes and outcomes of key UN and EU initiatives during the decade 2002-2011 in regard to the development and acceptance of human rights responsibilities for business enterprises. That decade saw a change from rejection to welcoming of ideas on such responsibilities as a key social sustainability issue. Demonstrating the use of systems theory to empirical cases, the article shows how the systems theory perspective generates important insights on communicative aspects of a regulatory process towards a normative change in contexts with multiple and diverse interests at play in today’s legal order where the transnational character of many sustainability problems exceeds the nation state. The article fills a knowledge gap concerning processes for governing transnational sustainability issues, where the territorial limits of national public law and the weak private-actor coverage of international law pose challenges to conventional regulation.